AUTHORITY TO ACT HUSBAND OR WIFE IN MAKING A DEED OF TESTAMENTARY ESTATE (LEGAAT) ON JOINT PROPERTY IN MARRIAGE - Jassica Halim; Ahmadi Miru; Nurfaidah Said (Sekolah Tinggi Ilmu Hukum Awang Long, 2022)
The purpose of this study was to analyze the actions of the husband or wife in making a deed of the testamentary estate of joint property in marriage. This type of research is normative-legal research, using a legal approach, a conceptual approach, and a case approach. The legal materials used are primary legal materials and secondary legal materials, using library research techniques, qualitatively analyzed using prescriptive presentation techniques. The results showed that the husband or wife's authority to act in making a deed of the testamentary estate (legaat) on joint property in a marriage, namely a capable husband or wife and a lamp to act alone without requiring the approval of the wife or husband, as long as what was granted in the will only and part-owned by husband or wife over the object of joint property in marriage, because if the deed of grant of will on joint property in a marriage is made jointly by husband and wife or made by husband or wife with the consent of the wife or husband, then on the deed of grant of will it will be in danger of being canceled.